Perhitungan Harga Pokok Produksi Dengan Metode Full Costing Pada Umkm Budidaya Ikan Mas Koki “Nanda” Desa Pagersari, Kecamatan Kalidawir, Kabupaten Tulungagung - Nanda Akbar Wijaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The use of the full costing method in calculating the cost of production is more precise and accurate. This is because the full costing method includes all detailed cost components for the production process. This study aims to analyze the comparison of the cost of production according to the UMKM Nanda Goldfish and the calculation of the cost of production according to the full costing method. The data used in this research is primary data. The method of data analysis technique used is a qualitative descriptive analysis method. The contribution in this research is to help the UMKM Nanda Goldfish to get the right calculation of the cost of production. The results showed that the calculation of the cost of production using the full costing method was higher than the calculation of the cost of production using the UMKM Nanda Goldfish method. The results show that the calculation of the cost of production using the full costing method is Rp. 1,066 and the calculation of the cost of production is using the UMKM Nanda Goldfish method which is Rp. 543. This is because the UMKM Nanda Goldfish/1only includes direct material costs for seeds, labor costs, and electricity overhead costs. Without including feed raw material costs, vitamin overhead costs, pharmaceutical overhead costs, plastic overhead costs, and oxygen overhead costs. Keywords: Cost of production, Full Costing Method